The Morals Strategies from Sunnah Depending (Journal Of Educational and Psychological Researches, 2022)
The study aims at elicitation the morals strategies from sunnah depending on the analytic-qualitative method. It revealed a comprehensive integrated system of creative strategies to improve morals. It was categorized into three areas: cognitive strategies, affective strategies, and some strategies based on self-initiative and practice. The researcher recommended that teachers and educators should employ these effective strategies in the process of moral guidance for the Muslim generation. He also recommended that researchers should put more effort to do more In-depth qualitative studies, which must be directed to establish the origin of different education strategies from the Holy Qur’an, the Sunnah, and Muslim scholars’ legacy.